Aktifitas Fisik Menjadi Faktor Dominan Kejadian Hipertensi pada Pasien Rawat Jalan di Puskesmas Kecamatan Cipayung Periode Januari-April Tahun 2023 - putra, sukma aditya; Notoatmodjo, Soekidjo; Sulistyowati, Yeny (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
Hypertension is an increase in systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg. The long-term impact of high blood pressure can lead to damage to various organs such as the heart, kidneys, and brain. In 2019, 34 percent of the population in Jakarta experienced the risk of hypertension, both mild and severe. Based on data from the Cipayung District Health Center in 2022, hypertension ranked first among the top 10 most frequently visited diseases on a monthly basis. This research aims to study and explain the relationship between lifestyle and the occurrence of hypertension in outpatients at the Cipayung District Health Center during the period of January-April 2023. The study design of this research is cross-sectional. Data collection is sourced from secondary data obtained from the medical records of the Cipayung District Health Center. The population in this study consists of outpatients who visited the Cipayung District Health Center with data collected from January to April 2023, totaling 1152 individuals, and all of them were analyzed. Based on the analysis results, it is known that age, gender, education level, physical activity, and salt consumption significantly influence the occurrence of hypertension. Physical activity is the most dominant risk factor influencing the occurrence of hypertension with an odds ratio of 29.714 and a 95% confidence interval of 19.543 - 45.178. Therefore, it is expected that the health center can enhance health promotion efforts and interventions targeting at-risk groups to prevent hypertension in the Cipayung Health Center area. Additionally, establishing sports clubs and healthy Diet Community Kitchens that can be participated in by the community can be beneficial. Increasing community engagement in healthy living can also reduce the risk of hypertension in the population. Keywords : Hypertension, Physical Activity, Health Center, Cipayung